AstroSat observations of interacting galaxies NGC 7469 and IC 5283 - Samantaray, Abhinna Sundar; Jassal, H. K.; Singh, K. P.; Dewangan, G. C. (Astronomy and astrophysics, 2024)
Aims: We carry out deep near-ultrviolet (NUV) and far-ultrviolet (FUV) imaging of an interacting galaxy system, comprised of a Seyfert type 1 galaxy NGC 7469 and its companion IC 5283. Our aim is to resolve and map the star-forming regions in the outer arms and look for signs of interaction between the two galaxies. Methods: We used AstroSat Ultra Violet Imaging Telescope (UVIT) to obtain NUV and FUV images of NGC 7469 in a range of filters. We have carried out photometry of star-forming regions in the two galaxies and found their spatial distributions. We also obtained the distributions of star formation rates (SFR) in NGC 7469 and IC 5283 using the estimates obtained from the FUV and NUV bands. We also carried out Kolmogorov-Smirnov tests to look for differences in the SFRs in the two galaxies. We derived the spectral energy distribution (SED), leading to the determination of physical parameters, including the overall SFR, stellar mass M*, dust mass M Dust, and specific star formation rates (sSFRs) in both the galaxies. Results: Our NUV and FUV images show the presence of an outer spiral arm that is better resolved. We have identified 33 new star-forming regions out of 51 total identified in the UVIT composite image. Enhanced star formation activity is observed to coincide with the interaction, and KS tests show that there are no significant differences in the SFR distributions of NGC 7469 and IC 5283, indicating that the interaction between the galaxies has not influenced their star formation processes differently. The SED plots and the photometric results demonstrate that most of the star formation activity is confined inside the central starburst (SB) ring.